Research on the Safe Broadcasting of Television Program - Song Jin Bao; Song Jin Hong; Chai Jian Ping (MATEC Web of Conferences, 2016)
The existing way of broadcasting and television monitoring has a lot of problems in China. On the basis of the signal technical indicators monitoring in the present broadcasting and television monitoring system, this paper further extends the function of the monitoring network in order to broaden the services of monitoring business and improve the effect and efficiency of monitoring work. The problem of identifying video content and channel in television and related electronic media is conquered at a low cost implementation way and the flexible technology mechanism. The coverage for video content and identification of the channel is expanded. The informative broadcast entries are generated after a series of video processing. The value of the numerous broadcast data is deeply excavated by using big data processing in order to realize a comprehensive, objective and accurate information monitoring for the safe broadcasting of television program.